Simultaneous Measurement of Pressure and Temperature Based on Adjustable Line Scanning Polarized Low-Coherence Interferometry With Compensation Plate - Tiegen Liu; Chi Zhang; Shuang Wang; Junfeng Jiang; Kun Liu; Xuezhi Zhang; Xue Wang (IEEE Photonics Journal)
A novel method realized by an adjustable line scanning polarized low-coherence interferometer is proposed and experimentally demonstrated to simultaneously measure pressure and temperature. The combination of birefringence wedge and compensation plate acts as an adjustable line scanning part to adapt various sensors by changing the thickness of compensation plate. The variations of pressure and temperature manifest as shift of the corresponding interference fringes on an infrared line array CCD. The dual-light-source is employed to fix the over occupation of CCD caused by an SLD with longer coherence length than an LED and enlarge the measuring range. An experiment of pressure and temperature was carried out to verify the effectiveness of the proposed method. The experimental results show that the proposed method is appropriate for the simultaneous measurement of pressure and temperature, and the sensor has a good linearity in pressure range of 3–228 kPa and temperature range of −20 °C −70 °C. The measurement errors of the pressure and temperature are less than 0.3%F.S. and 1.1%F.S., respectively.